Failure patterns of dual headed bars in concrete loaded in tension and compression - A. Abdulhamed, Ayman; H. Saeed, Haitham (International Journal of Engineering and Technology, 2019)
Headed bars are used as an alternative to hooked bars and reduce steel congestion and fabrication difficulties in reinforced concrete joints. But, according to the ACI 318 code, classical headed bars cannot be used to develop bars when they are subjected to compression loading. The use of dual headed bars can provide a solution to anchorage problems for bars loaded in compression. This paper presents comparison of failure patterns for classical single headed bars and dual headed bars loaded in tension and compression. The results showed that dual headed bars exhibited significant higher anchorage capacity than classical single headed bars loaded in compression. No improvement, or even slightly lower anchorage strength was recorded when dual headed bars were loaded in tension. The failure pattern in compression loading is improved a lot by using dual heads in which end blowout mode of failure is prevented.